Analysis of the Energy Storage Efficiency of a UAV-Mounted Sensor Launcher Built on Traditional Crossbow Launch Mechanisms - Yanan He; Huiqi Xu; Lei Wang; Lingsong Di; Weihua Liu; Liang Liu (Drones)
Deploying sensors to target locations using UAV platforms can effectively address the issue of limited aerial endurance in micro-UAVs. This paper introduces a launch method based on the crossbow principle, which is capable of concealing the deployment of heavy sensors. Given that the size and mass of the launcher on the UAV should be minimized, optimizing the structural energy storage performance of the launcher is essential. Initially, a static energy storage model for the launcher was developed, and criteria for evaluating the energy storage coefficient were established. Using the control variable method, the impact of seven structural parameters on the energy storage performance was analyzed. Based on these findings, a particle swarm optimization algorithm was proposed to optimize six parameters, aiming to maximize the energy storage coefficient. Subsequently, the bending stiffness coefficient of the launcher’s bow limb can be adjusted according to the specific application scenario to manage the energy storage within a reasonable range. Calculations revealed that after optimization, the maximum draw force was only 0.675 times that of the original plan under the same energy storage conditions. With the same maximum draw force, the energy storage capacity was 1.5 times higher than the original plan, indicating a significant optimization effect. This optimization approach provides a theoretical foundation for the energy storage optimization analysis of UAV-launched crossbow-based systems.